Wnt5a expression and prognosis in stage II–III colon cancer - Lund, Cecilia Margareta (Transl Oncol, 2020)
Cancer metastases accounts for most cancer deaths. The secreting glycoprotein Wnt5a impairs tumor cell migration and reduces invasiveness and metastasis. High Wnt5a expression in tumor cells is correlated to better outcomes in patients with breast, prostate and epithelial ovarian cancer. We aimed to investigate the association between the Wnt5a expression and outcomes in patients with colon cancer (CC) stage II/III. We performed a retrospective single-center study evaluating 345 patients with radical resection for primary CC, stage II/III, who started 6 months of adjuvant chemotherapy with 5-FU or capecitabine ± oxaliplatin between 2001 and 2015. Archived formalin-fixed paraffin embedded tumor tissue from resection specimens were stained with Wnt5a antibody using immunohistochemistry. Cytoplasmatic Wnt5a staining was assessed according to intensity and percentage of stained cells. Patients were divided in groups depending on high (n = 230) or low (n = 115) Wnt5a expression. Disease free survival (DFS) and overall survival (OS) were analyzed for the two groups using Kaplan-Meier plots and Long rank test. Patients with Wnt5a-negative tumors had significantly poorer performance status (PS) than patients with high Wnt5a expression (p = 0.046). No significant difference was seen between patients with low and high Wnt5a expression in terms of 5-year DFS (p = 0.517) or 5-year OS (p = 0.415). Poor PS was associated with lower DFS (p = 0.002) and OS (p < 0.001). In conclusion, we found no significant difference in prognosis for patients with stage II/III CC depending on their Wnt5a expression. Patients with Wnt5a-negative tumors had significant poorer PS than patients with higher levels. Poor PS was associated with lower DFS and OS.